Norway’s Foreign Policy in the Twentieth and Twenty-first Centuries Noble Rhetoric and National Interests - Almlid, Geir K. (Springer International Publishing : Imprint: Palgrave Macmillan, 2024)
X, 240 p. 1 illus.